Early, patient-initiated treatment of herpes labialis with topical 10% acyclovir. - Spruance, S L (1984)
To determine whether topical acyclovir in polyethylene glycol could reduce the severity of herpes simplex labialis if applied immediately after onset of a recurrence, 10% acyclovir in polyethylene glycol ointment or polyethylene glycol alone was prospectively dispensed to 352 patients in a double-blind, randomized trial. Sixty-nine subjects initiated treatment in the prodrome (57%) or erythema (43%) stage and were followed by clinical and virological criteria. The healing time (6.0 days), maximum lesion area (42 mm2), vesicle or ulcer formation (91%), and maximum lesion virus titer (4.8 log10 PFU) in the drug recipients were not reduced in comparison with those who received the vehicle (5.2 days, 30 mm2, 75%, and 4.5 log10 PFU, respectively). Topical acyclovir in polyethylene glycol was ineffective for the treatment of herpes labialis despite an optimum therapeutic opportunity.